Volume 6: Ceramics; Controls, Diagnostics and Instrumentation; Education; Manufacturing Materials and Metallurgy; Honors and Aw 2015
DOI: 10.1115/gt2015-42139
|View full text |Cite
|
Sign up to set email alerts
|

Gas Turbine Exhaust Temperature Measurement Approach Using Time-Frequency Controlled Sources

Abstract: Siemens has developed a novel approach for measuring the process gas temperature leaving the power turbine in their heavy industrial gas turbine engines using active acoustic tomography. Siemens has deployed this measurement technique on two test engines of different power ranges and different combustion and exhaust duct configurations. These engine tests have demonstrated that this technology is effective and robust. All working parts are outside the heat effective zone so, unlike the traditional intrusive po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In this study, an acoustic pyrometer similar to the one proposed by DeSilva et al [7,8] was considered. Therefore, heavy-duty gas turbine exhaust was assumed to flow inside a stainless-steel pipe with a diameter of 1 m. The temperature and pressure of the turbine exhaust were supposed to be Texh = 813.15 K and pexh = 101325 Pa, respectively, whilst the gas relative humidity was considered RH = 70%.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, an acoustic pyrometer similar to the one proposed by DeSilva et al [7,8] was considered. Therefore, heavy-duty gas turbine exhaust was assumed to flow inside a stainless-steel pipe with a diameter of 1 m. The temperature and pressure of the turbine exhaust were supposed to be Texh = 813.15 K and pexh = 101325 Pa, respectively, whilst the gas relative humidity was considered RH = 70%.…”
Section: Case Studymentioning
confidence: 99%
“…They pointed out how, conversely to traditional methods, the technique is suitable for control as it does not suffer thermal lag. DeSilva et al [6,7] successfully used the method to measure a heavy-duty gas turbine's exhaust gas temperature distribution. In their investigation, they underlined how the turbomachinery's flow velocity, mass flow and turbulence levels require alternative sound signals conversely to highintensity pulses typically used in furnaces and boilers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of acoustic measurements for nonintrusive gas turbine engine flow monitoring has been proposed and several studies have been conducted to assess its feasibility in practical applications [1][2][3][4][5]. An acoustic approach is of par ticular interest because it offers several unique advantages over optical methods (such as particle image velocimetry) in gas turbine engine environments.…”
Section: Introductionmentioning
confidence: 99%
“…Reported results showed that acoustically measured gas turbine exhaust temper atures were within 10 °C of thermocouple data. Siemens conducted a similar study in 2015, this time using improved sound source design for better time-of-flight estimation, and reported 0.36% bulk mean temperature error in temperatures up to 600 • C [3]. In both experiments, the impact of flow velocity on the measurements was not addressed in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation